2008
DOI: 10.1016/j.rfe.2008.03.003
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the impact of timberland, farmland and commercial real estate in the asset allocation decisions of institutional investors

Abstract: We examine the effects of including timberland, farmland and commercial real estate in a mixed asset portfolio with stocks, government bonds and T‐Bills. Using both smoothed and unsmoothed returns (as per Geltner [Geltner, D. (1993). Estimating market values from appraised values without assuming an efficient market. Journal of Real Estate Research, 8, 25–345.]) and both constrained and unconstrained allocation assumptions (as per Eichhorn, Gupta and Stubbs [Eichhorn, D., Gupta, F., & Stubbs, E. (1998). Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…To our best knowledge, only a few studies examined NPI, NTI and NFI altogether. Waggle and Johnson (2009) investigated the effects of including timberland, farmland and commercial real estate in a mixed-asset portfolio with stocks, government bonds and Treasury bonds under the mean-variance efficiency framework using both smoothed and unsmoothed returns and with both constrained and unconstrained scenarios. They found that timberland was included in almost all portfolios but farmland and commercial real estate were only included in low-risk portfolios.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To our best knowledge, only a few studies examined NPI, NTI and NFI altogether. Waggle and Johnson (2009) investigated the effects of including timberland, farmland and commercial real estate in a mixed-asset portfolio with stocks, government bonds and Treasury bonds under the mean-variance efficiency framework using both smoothed and unsmoothed returns and with both constrained and unconstrained scenarios. They found that timberland was included in almost all portfolios but farmland and commercial real estate were only included in low-risk portfolios.…”
Section: Literature Reviewmentioning
confidence: 99%
“…higher expected returns, low associated risk, timber's economy, and inflation hedging) allow a portfolio with a timberland component of 10 percent to yield highly positive results. Zhang et al (2011) and Waggle & Johnson (2009) also find significant benefits when timberland is added into a portfolio of stocks, bonds, and T-bills. On the contrary, the analysis presented by Scholtens & Spierdijk (2010) concludes that, after removing the appraisal smoothing bias from timberland returns, there is no evidence that adding timber into a portfolio mix of traditional assets can increase mean-variance efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, when it comes to assessing other attributes of these assets for institutional investors, such as improving the returnto-risk characteristic or providing diversification, previous works present contradicting findings. On one side, Waggle & Johnson (2009), Healey et al (2005) and Kaplan (1985) argue that including natural assets in the SAA of institutional investors can yield to positive results by improving the risk-to-return relationship of their portfolio. On the contrary, Scholtens & Spierdijk (2010) suggest that timberland investments do not significantly improve the mean-variance efficiency of portfolios when removing the appraisal smoothing bias found in natural asset's returns.…”
mentioning
confidence: 99%
“…La and Mei (2015) found little evidence of cointegration between timberland REITs and S&P500 index, thereby suggesting some long-run diversification benefits of timberland REITs. However, only a limited number of studies have examined farmland and timberland assets together Waggle and Johnson, 2009;Zhang and Mei, 2019). Waggle and Johnson (2009) evaluated the performance of timberland, farmland, and commercial real estate within a multi-asset portfolio and found that timberland entered all portfolios, whereas farmland and commercial real estate only entered low-risk portfolios.…”
Section: Introductionmentioning
confidence: 99%